2014
DOI: 10.1007/s00776-014-0633-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of highly-bioavailable curcumin for treating knee osteoarthritis: a randomized, double-blind, placebo-controlled prospective study

Abstract: BackgroundWe previously developed a surface-controlled water-dispersible form of curcumin and named it Theracurmin® (Theracurmin; Theravalues, Tokyo, Japan). The area under the blood concentration–time curve of Theracurmin in humans was 27-fold higher than that of curcumin powder. We determined the clinical effects of orally administered Theracurmin in patients with knee osteoarthritis during 8 weeks of treatment.MethodsFifty patients with knee osteoarthritis of Kellgren–Lawrence grade II or III and who were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
200
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(213 citation statements)
references
References 24 publications
2
200
0
11
Order By: Relevance
“…37 We also excluded one study because there was no relevant outcome 38 and one (abstract) because it was a duplicate of another excluded study. 39 Finally, we included seven studies [40][41][42][43][44][45][46] with a total of 797 participants. Key details of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…37 We also excluded one study because there was no relevant outcome 38 and one (abstract) because it was a duplicate of another excluded study. 39 Finally, we included seven studies [40][41][42][43][44][45][46] with a total of 797 participants. Key details of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies the proportion of participants with bilateral knee OA ranged from 37% 44 to 100%. 45 Three studies 42,43,46 did not report the proportion of participants with bilateral knee OA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations